Enzymatic degradation of phytate, polyphenols and dietary fibers in Ethiopian injera flours: Effect on iron bioaccessibility. (1st May 2015) - Baye, Kaleab; Guyot, Jean-Pierre; Icard-Vernière, Christèle; Rochette, Isabelle; Mouquet-Rivier, Claire
Highlights: Flour blend composition influenced response to enzyme treatments. >90% removal of IP6 did not improve fractional iron bioaccessibility. Dietary fiber hydrolysis increased fractional iron bioaccessibility. Effect of polyphenol oxidase treatment on dialysable-Fe was food-matrix dependent. Abstract: The effect of removing phytate (IP6), iron-binding polyphenols, and dietary fibers on iron bioaccessibility in wheat-red sorghum (WrS) and teff-white sorghum (TwS) flour blends used in Ethiopia to make injera, a fermented pancake, was evaluated through the application of exogenous enzymes. Phytase treatment led to >90% reduction in IP6 and to an IP6:Fe molar ratio <1, but iron bioaccessibility was not improved ( P > 0.05). Phytase + xylanase + cellulase (P + X + C) treatment increased iron bioaccessibility in TwS (non-detectable to 1.6%) and WrS (1.9–3.2%), whereas phytase + polyphenol oxidase (P + PPO) treatment only showed improvement in the TwS blend. P + X + C + PPO treatment of the WrS blend increased the soluble non-dialysable iron fraction (6.7%) more than P + PPO treatment (3.9%). Although responses to enzyme treatments and iron bioaccessibility were matrix dependent, a positive effect of dietary fiber hydrolysis with X + C was obtained, irrespective of the blend. Dietary fibers had a negative effect on iron bioaccessibility independent of phytates.